Evaluation of Safety Performance in Provincial Road Network - Tharmarajah, S.; Pasindu, H.R. (University of Jaffna, 2022)
Provincial roads in Sri Lanka considered as class C and D which serves connection between urban and rural to ensure the social and economic necessities. Even though it is a developing country, the majority of these roads are in poor condition, and safety concerns are minimal. The lack of accurate accident data and the lack of a road condition monitoring program are frequently mentioned as factors. This study proposes a methodology to determine safety index to evaluate safety performance in provincial roads in Sri Lanka. Cumulative safety index is computed with the fundamental elements such as exposure, probability and consequences. Computed Cumulative Safety Index is compared with the available crash data. All severity levels are translated to a single scale termed Equivalent Property Damage Only (EPDO) to validate the results. Once the actual EPDO is calculated, multiple regression analysis tool is used to determine the relationship between actual EPDO and computed CSI composed of identified safety issues in the road segments. Actual EPDO and Estimated EPDO were compared using Root Mean Square Error (RMSE)
Keywords: Provincial Road; Safety Index; Equivalent property Damage Only; Root Mean Square Error